Adult Chronic Exposure to Neurotoxic Metals Associated with Atmospheric Aerosols: A Case Study in The Urban Area of Turin (NW Italy) - Casazza, Marco; Maurino, Valter; Malandrino, Mery (Journal of Environmental Accounting and Management, 2026)
Particulate Matter (PM) pollution still represents a great concern for its adverse effects on human health. Among the emerging risks, the neurotoxicity of PM-associated metals has been evidenced by the scientific literature. Since PM inhalation plays an important role with respect to its toxicity, there is a recognized need for improving the studies with respect to its deposition sites. This work is focused on the assessment of PM10- associated metals in the urban environment of Turin (NW Italy), one of the most polluted European areas. Data of PM10-associated metals mass size distribution, percentage repartition associated to the respiratory apparatus, relative concentration peaks, together with preferential deposition sites and the daily inhaled dose have been calculated. The analyzed metals were: As, Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Sn, V and Zn. The data are limited, considering a precautionary approach, to the winter season, when the intensity and number of sources is greater and only in the case of stable good weather conditions, when the atmospheric removal processes have a more limited impact on the aerosol dynamics. The results show that the element concentrations in Torino atmospheric PM are similar to those of other considered European towns. The measures evidence a preferential association of each metal with different areas of the respiratory apparatus Furthermore, ordering the analyzed metals with respect to the daily inhaled dose, from higher to lower, we have: Fe, Zn, Sn, Cd, Mn, Cu, Pb, Ni, Cr, Mo, V, As and Co. Even if the risk doesn’t seem to be significant up to now (apart from Cr), the evolving knowledge on the effects of chronic sub-threshold exposure might give a different evidence in the future. PM10 size repartition measurement, together with the analysis of PM10-associated compounds, could well intermittently complement the routine air quality measures with the purpose of increasing the present body of knowledge with respect to PM neurotoxicity, allowing to improve both the existing risk assessment procedures and the public health management.